Hemingway : the writer as artist - Barker, Carlos (New York : Princeton University Press, 1963)
As medical advances become more sophisticated, average life expectancies continue to grow. This presents significant challenges to the health care system, and caring for older people is now every nurse's concern. This book aims to help nursing students understand how to care for older people in any care setting. It uniquely focuses on person-centered, humanized care in addition to physical care, helping students to examine attitudes towards older people in health care and combat negative stereotypes. The book takes a positive stance on aging, celebrating the fact that in the Western world we live longer and healthier with a focus on the well-being of the individual. Key features: easy-to-read introduction for nursing students, with a chapter on making the most of placements with older people; linked to the latest NMC Standards and Essential Skills Clusters for degree-level education; theory is linked to practice through case studies and scenarios, emphasizing the lived experiences of the older person; plenty of activities help build critical thinking and graduate skills. -- Provided by publisher.
Foreword -- About the authors -- Acknowledgements -- Context of nursing older people / Ann Hemingway -- Placement experiences with older people / Karen Cooper-- Vulnerability and old age / Vanessa Heaslip -- Nursing for well-being in later life / Ann Hemingway and Rosalind Green -- Physical aspects of aging / Michele Board and Karen Cooper -- Psychosocial aspects of aging / Lee-Ann Fenge -- Mental health and emotional well-being in later life / Sue Barker -- Aging in a multicultural society / Janet Scammell -- Social Isolation and loneliness in later life / Eleanor Jack -- Inter professional collaboration when working with older people / Sarah Hean and Sue Smith -- Glossary -- References -- Index.
Includes bibliographical references (pages 213-232) and index.
Text in English.